Race, Class, and the Politics of Decolonization Jamaica Journals, 1961 and 1968 - Clarke, Colin; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book offers a detailed picture of Jamaica before and after independence. A 1961 journal sheds light on the political and social context before independence, while a 1968 journal shows how independence dissolved dissident forces and identifies the origins of Jamaica's current two party politics.
Keywords: Social sciences; Political science; Political theory; Political economy; World politics; Social structure; Social inequality; Ethnicity; Social Sciences; Social Structure, Social Inequality; Ethnicity Studies; Political Theory; Political Science; Political Economy; Political History; Electronic books